Peran Inovasi Teknologi Dalam Meningkatkan Kualitas Pendidikan Indonesia di Era Digital - Rizqa Mardhiah; Sahrul Hidayat; Vini Febrianty; Sofyan Iskandar (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The development of digital technology has had a significant impact on various aspects of life, including the field of education. In this context, technological innovation has become an urgent necessity to improve the quality of national education that is adaptive to the changing times. Technology not only provides learning tools but also paves the way for a comprehensive transformation of the curriculum. A digital curriculum enables learners to acquire 21st-century skills such as critical thinking, collaboration, creativity, and communication. This study aims to explore the role of technological innovation in enhancing the quality of education in Indonesia in the digital era. The research method used is descriptive qualitative with a literature review approach. Data were collected from scholarly journals, books, and relevant documents for in-depth analysis and understanding. The findings indicate that technological innovation has a positive impact on more equitable access to education, technology-based learning, personalized learning, and innovation in assessment. The integration of e-learning platforms, collaborative educational applications, and open-access resources expands educational resources and fosters an inclusive learning environment. However, there are significant challenges such as the digital access gap, low digital literacy, resistance to change, and data security issues. Therefore, the implementation of technological innovation in education requires synergy among various stakeholders: the government, educators, society, and educational institutions. Curriculum changes that incorporate technology must be accompanied by ongoing teacher training and strengthened digital infrastructure. In conclusion, the role of technological innovation is crucial in creating an inclusive, effective, and responsive education system in the digital age.